The maintenance management of marine port facilities : case study Kuantan marine port - Muhammad Zulhilmi, Nordin (2010)
Nowadays, facility management plays an important role in building industries in Malaysia. It become importance for many building owner especially building or facility involve in 24 hours everyday operation. For this reason, it should have a good maintenance services to sustain the function of all facilities in building whereby it will fulfil building users need. The effectiveness of the aspects of maintenance such as planning, supervision and organization management will maintain the building quality performance all the times. In order to determine the maintenance aspects in facility management, a case study was conducted on Kuantan Port, Pahang. The data was collected via interview with people who involved in maintenance management and also identify the system of maintenance works. Based on the case study, it found that the maintenance aspects in facilities management of Kuantan Port consist of planning, maintenance work system, scheduling of work and work record. The result from this study, the aspects of maintenance can influence the maintenance costs base on the annual maintenance cost. In this study, several improvements to existing building maintenance management have been identified. It is useful as a guideline for an effective facilities and maintenance management.